Preperitoneal onlay mesh repair for ventral abdominal wall and incisional hernia: a novel technique. Issue 4 (November 2016) - Yang, PC George; Tung, LM Karen
Abstract: Introduction: Intraperitoneal onlay mesh repair is a current technique for laparoscopic repair of ventral and incisional hernias. However, the placement of synthetic mesh intraperitoneally may potentially lead to mesh‐induced complications such as adhesive intestinal obstruction, enterocutaneous fistula, or even mesh erosion into organs. Inspired by the concept of laparoscopic inguinal hernia repair, we developed a novel technique: preperitoneal onlay mesh repair (PPOM). This involves placing the mesh in the preperitoneal plane to help eliminate mesh‐induced complications. Material and Surgical Technique: Our first case of PPOM was performed on a 54‐year‐old woman who developed a complex incisional hernia after multiple abdominal operations. The total size of the hernia defect was 8 × 13 cm. The peritoneal flap was carefully created with synthetic mesh placed on the preperitoneal plane, and then it was completely closed with sutures. The patient had an uneventful recovery except for a small seroma. Discussion: We herein report the first case of incisional hernia successfully treated by this novel technique, PPOM. We explain the reasons to perform PPOM, the advantages it offers, and why we named this novel technique "PPOM."